ACTOR CONTESTATION IN MANAGEMENT OF THE PASIR PUTIH BEACH TOURIST ATTRACTION IN PANDEGLANG REGENCY - Saputra, Ahmad Andi; Mayrudin, Yeby Ma'asan (Journal of Social Politics and Governance (JSPG), 2024)
Power relations between actors can be explored starting from positions, roles, interests and various actions carried out by different actors. The aim of this research is to determine the mapping of government, private and community actors in managing the Pasir Putih Beach tourist attraction. Using the actor mapping framework theory and which states that contestation has several key terms, namely habitus, arena (field), and capital symbol, and finally using lewis coser's conflict theory, namely realistic conflict and non-realistic conflict. Qualitative research method with a case study approach. The results of this research show that the role of actors is still not moving well towards something positive, contestation between actors is clearly visible with the opening of illegal tourist attractions by the community. The role of the government as the front guard in finding solutions to conflicts here is still very minimal, the government has not been able to encourage discussions between actors to minimize conflicts. There needs to be awareness from government, private and community actors in order to create tourist attractions that can benefit the village. The government seems to be silent and appears to be siding with entrepreneurs, causing people to make decisions outside of the specified policies.